Leaders' innovative problem-solving styles among participants of the National Principalship Qualification for Educational Leaders (NPQEL) program - Hamidon bin A. Rahman (Kulliyyah of Education, International Islamic University Malaysia, 2016)
This study primarily aims to understand educational leaders' innovative problem-solving styles among participants of the National Principalship Qualification for Educational Leaders (NPQEL) program. Firstly, it aims to explore their perceptions of the changes that are happening in education and how they cope with the changes. Finally, it seeks to examine factors that influence innovative problem-solving styles and validate the model of innovative leadership. The respondents consisted of nine school principals who have been nominated for innovative leader award and two cohorts of National Principalship Qualification for Educational Leaders (NPQEL) program. The data was collected through a mixed method approach: semi-structured questions and questionnaires. Interview transcripts are analysed and emerging themes were clustered with several topics. Data from the Questionnaires were analysed using Principal Component Analysis and Confirmatory Factor Analysis to confirm the model fit. Finally, data was calculated for reliability and validity using discriminant validity test. The key findings showed that participants' perceptions of the changes were positive and they accept the fact that changes are important for improvements. Secondly, participants cope with the changes by learning new skills, creating experts teams and utilising the stakeholders. Thirdly, among the traits associated with innovative behaviour include self-confidence, boldness, perseverance, problem-solver, think-outside-the-box attitude, interaction with teachers, gradual implementation of innovative projects and principal as catalyst for change. Overall, the findings from this investigation can be utilised to measure innovative problem-solving styles among Malaysian school leaders.